2009
DOI: 10.1007/s11207-009-9424-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of EUV Coronal Jets Observed with STEREO/SECCHI

Abstract: In this paper we present the first comprehensive statistical study of EUV coronal jets observed with the SECCHI (Sun Earth Connection Coronal and Heliospheric Investigation) imaging suites of the two STEREO spacecraft. A catalogue of 79 polar jets is presented, identified from simultaneous EUV and white-light coronagraph observations, taken during the time period March 2007 to April 2008, when solar activity was at a minimum. The twin spacecraft angular separation increased during this time interval from 2 to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
201
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(216 citation statements)
references
References 22 publications
15
201
0
Order By: Relevance
“…The authors depicted a helical structure of a jet, which showed signs of untwisting with the jet initially ascending slowly with ≈10−20 km s −1 and then suddenly accelerating to velocities higher than 300 km s −1 . Helical structures in jets have also been reported by Shimojo et al (1996), Jiang et al (2007), and Nisticò et al (2009). Kamio et al (2010) studied the relation of so-called macrospicules in He ii 304 Å and an X-ray jet.…”
Section: Introductionmentioning
confidence: 83%
“…The authors depicted a helical structure of a jet, which showed signs of untwisting with the jet initially ascending slowly with ≈10−20 km s −1 and then suddenly accelerating to velocities higher than 300 km s −1 . Helical structures in jets have also been reported by Shimojo et al (1996), Jiang et al (2007), and Nisticò et al (2009). Kamio et al (2010) studied the relation of so-called macrospicules in He ii 304 Å and an X-ray jet.…”
Section: Introductionmentioning
confidence: 83%
“…Jets occur prolifically across the solar surface, most notably within coronal holes and around the periphery of active regions (Shimojo et al 1996;Savcheva et al 2007). They are observed in X-rays (e.g., Shimojo et al 1996;Cirtain et al 2007) and at a variety of extreme-ultraviolet (EUV) wavelengths (e.g., Nisticò et al 2009;Zhang et al 2016), reflecting the fact that some jets possess both hot and cool (relative to the ambient corona) components. Some jets are energetic enough to reach the heliosphere and become visible as jet-like coronal mass ejections (CMEs) in white-light coronagraphs (e.g., Wang et al 1998;Patsourakos et al 2008;Hong et al 2011;Moore et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Using the Solar Terrestrial Relations Observatory (STEREO; Kaiser et al 2008) twin inner coronagraphs (COR1; Thompson et al 2003) Nisticò et al (2009 studied various aspects of jets, including their correlation with underlying small scale chromospheric bright points. More recently, Pucci et al (2012) have presented an analysis of the correlation of X-ray bright points and jets observed by Hinode/XRT and concluded that most of the jets occurred in close temporal association with the brightness maximum in bright points.…”
Section: Introductionmentioning
confidence: 99%